Perspectives on Jewish Music: Secular and Sacred - Friedmann, Jonathan L. (Lexington Books, 2009)
Perspectives on Jewish Music presents five unique and engaging explorations of Jewish music. Areas covered include self-expression in contemporary Jewish secular music, the rise of popular music in the American synagogue, the theological requirements of the cantor, the role of women in Sephardic music and society, and the personal reflections of a leading figure in American synagogue music. Its wide-ranging topics and disciplinary approaches give evidence for the centrality of music in Jewish religious and secular life, and demonstrate that Jewish music is as diverse as the Jews themselves. From these studies, readers will gain an appreciation of both what Jewish music is and what it does. This book will be useful for students, practitioners, and scholars of Jewish secular and religious music and Jewish cultural studies, as well as ethnomusicologists specializing in Jewish or religious music.